The role of cooperative learning in teaching floral vegetal motifs (Journal of the College of Basic Education, 2022)
This research aims to identify (the effectiveness of cooperative learning in the implementation of plant motifs for Arabic calligraphy and decoration).To achieve the aim of the research, the researcher put the following two zero hypotheses:1- There are no statistically significant differences between the mean scores of students in the experimental group who study plant motifs according to cooperative learning, and the mean scores of students in the control group who study the same subject in the usual way, in the post-cognitive test.2- There are no statistically significant differences between the mean scores of students of the experimental group who study plant decorations according to cooperative learning, and the mean scores of students of the control group who study the same subject in the usual way, in the post-skill test.